(untitled) (Proceedings of International Educators Conference, 2022)
When we think of classic poets, Anbar Otin, Uvaysi, Nodirabegim and Zebiniso come to our eyes. But there is another writer who has a special place in the history of our statehood, whose name is hardly found in the sources. Information about the work and activities of Kambarniso, who is mentioned as Muqimi’s relative, is mentioned in this article.